Serological Biomarkers and Their Detection in Autoimmune Bullous Skin Diseases - Heckler, Ilana; Hong, Michael; Sinha, Animesh; Venkataraman, Iswariya (Dermatology Practical & Conceptual, 2022)
Autoimmune bullous diseases (AIBDs) are a group of skin-related disorders that involve damage to structures maintaining cell-cell adhesion, such as desmosomes and hemidesmosomes. Key autoimmune bullous diseases include pemphigus related diseases, pemphigoid related conditions, acquired epidermolysis bullosa (EBA), and dermatitis herpetiformis (DH). Each group of conditions exhibits characteristic clinical lesion patterns and is associated with specific autoantibodies targeting epidermal and dermal structures involved in cell-cell adhesion and skin integrity. Pemphigus diseases primarily target desmoglein (Dsg) 3 and Dsg1 proteins but several non-desmoglein autoantibodies have also been linked to pemphigus. Pemphigoid diseases typically target BP (bullous pemphigoid)180 and BP230; EBA is associated with antibodies directed against anti-type VII collagen; and DH by IgA autoantibodies against tissue transglutaminase and deaminated gliadin. Investigation into the serological biomarkers found in autoimmune bullous diseases have allowed the development of diagnostic assessments (ie. tissue antibody detection and serological testing) based on the unique autoantibody profiles of a particular disease group. The methods for the detection and quantification of disease-associated autoantibodies continue to evolve and improve.